Public Services Motivation (PSM) in One Stop Integrated Services in Merauke Regency - Andri Irawan; Burhanudin Mukhamad Faturahman (Universitas Sultan Ageng Tirtayasa, 2019)
Implementation of Public Services Motivation (PSM) is a necessity for the Office of Investment and One Stop Integrated Services (DPMPTSP) where this organization has integrated services both central and local. The research objective is to analyze the application of the PSM principles in DPMPTSP service performance in Merauke Regency using descriptive methods and qualitative approaches. The results showed that the principles of PSM have not been fully implemented by DPMPTSP Merauke Regency. As for the principles that are implemented quite well that is seen from the indicators of commitment to public interest, empathy and self-sacrifice. But for indicators of employee interest only at the level of duties and orders from the supervisor of each section only because most of their time has been taken to carry out the tasks assigned. For this reason, increasing employee interest in providing services is very important so that DPMPTSP of Merauke Regency can serve the community well and have an impact on employees to improve their performance.